Africa Fertilizer and Soil Health Action Plan: Outcome 3 - African Union Development Agency- NEPAD (2024)
This poster presents Outcome 3 - ‘Greater Efficiency, Resilience and Sustainable Use of Mineral and Organic Fertilizer Inputs and Enhancement of Soil Health Interventions’ of the Africa Fertilizer and Soil Health (AFSH) Action Plan. It gives the AFSH Action Plan’s Vision, Expected Impact, Strategy and the contributing Outcome 3 with associated Outputs (3.1 – 3.4) and Action areas.